2008
DOI: 10.4028/3-908451-59-0.707
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Thixoforging of 7075 Aluminium Alloys at High Solid Fraction

Abstract: Abstract. Thixoforging is a type of semi-solid metal processing at high solid fraction (0.5 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
7
0
4
Order By: Relevance
“…But some non recrystallized grains remain for short cycle on the axis of the slug due to the low energy stored in the axis during extrusion. We will observe influence of these elongated grains on thixoforged parts [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But some non recrystallized grains remain for short cycle on the axis of the slug due to the low energy stored in the axis during extrusion. We will observe influence of these elongated grains on thixoforged parts [6].…”
Section: Resultsmentioning
confidence: 99%
“…There are no major impacts on the microstructure (grain size, shape or solid fraction). A few unrecrystallised grain remain but their resistance to the material flow during thixoforging should be minor due to their low thickness [6]. A seven step heating cycle is used to approach slowly, in a homogeneous way, a target temperature whilst allowing kinetic transformations like the solid-liquid transition to occur.…”
Section: Discussionmentioning
confidence: 99%
“…the migration of the high angle boundary) to occur [2,5]. Thixoforming involves forming alloys in the semisolid state to near net shaped products [6][7][8]. The required spheroidal microstructure can be obtained by a number of routes, including the Strain Induced Melt Activated method (SIMA) [9] and Recystallisation And Partial melting (RAP) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vaneetveld et al found that superior mechanical properties resulted from the use of a higher tool temperature setting and appropriate tool punch speed during thixoforming [10]. These settings so adjusted resulted in reduced cracking which was noted to occur due to overly fast cooling rates.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium 7075 has recently been investigated for use in the of semi-solid metal (SSM) processing [7][8][9][10][11][12]. The performance of aluminium 7075 was investigated using both thixoformed cooling slope and recrystallization and partial melting (RAP) route in order to compare their mechanical properties [7].…”
Section: Introductionmentioning
confidence: 99%